2011
DOI: 10.5712/rbmfc6(19)390
|View full text |Cite
|
Sign up to set email alerts
|

DECLARAÇÃO DE BRASÍLIA "O Conceito de rural e o cuidado à saúde"

Abstract: O Grupo de Trabalho (GT) de Medicina Rural, vinculado à Diretoria de Medicina Rural da Sociedade Brasileira de Medicina de Família e Comunidade (SBMFC), apresenta as seguintes características:VisãoExcelência em saúde rural para a população no Brasil.MissãoPromover a qualificação e a excelência da saúde rural no Brasil, respeitando a diversidade de cada região.Objetivos•     Tratar das questões de interiorização da Medicina de Família e Comunidade.•     Estimular o uso de tecnologias apropriadas para superar ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
9

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
0
5
0
9
Order By: Relevance
“…Assim, os profissionais de saúde que atuam neste contexto devem desenvolver habilidades específicas de atuação, visto as situações às quais são expostos continuamente. O profissional deve utilizar de forma ampliada suas habilidades para assistir de forma integral o idoso, incluindo aspectos culturais no cuidado (28) .…”
Section: Discussionunclassified
“…Assim, os profissionais de saúde que atuam neste contexto devem desenvolver habilidades específicas de atuação, visto as situações às quais são expostos continuamente. O profissional deve utilizar de forma ampliada suas habilidades para assistir de forma integral o idoso, incluindo aspectos culturais no cuidado (28) .…”
Section: Discussionunclassified
“…Lack of access to health care, related not only to geographic barriers but also to cultural aspects of local communities, is one of the mainimpediments to continuousquality improvement of vital statistics data 20,21 . Data from the Proactive Search of Deaths, gathered during the household interview phase, revealed that the main reason families gave for not report an infant death to a hospital or a vital statistic registrar was that they "felt no need to register the death of the child".…”
Section: Discussionmentioning
confidence: 99%
“…In these municipalities, the majority of the population live on the banks of rivers, many peoples are indigenous, the river being their main means of transportation. In view of the great difficulty of movement, lack of adequate infrastructure, extreme climatic conditionsconstant heat and rainfall -and geographic isolation in the region, access to healthcare is very problematic 22,23 . In addition to unregistered burials, a focused proactive search enabled the identification of cultural aspects of indigenous communities, which influence the information on vital events and the monitoring of the health situation.…”
Section: Discussionmentioning
confidence: 99%